Effect of Temperature Changes on Corrosion Rate in Motorcycle Exhausts - Ade Afriadi AR; Remon lapisa; Retno Wahyudi (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2021)
This study aims to determine the effect of temperature changes on the corrosion rate of motorbike exhaust. In this experimental study, the test specimens were given heat treatment by burning directly using solder gas, then immersed directly into a container containing plain water and salt water. After being given the treatment, an evaluation was held to see how much influence it had. On the 12th day of testing, all specimens experienced a decrease in weight, with details in specimen A experiencing a weight loss of 0.5 grams from the initial weight of 32 grams, with a corrosion rate of 0.064942241mm / year. Specimen B experienced a weight loss of 0.31 grams from the initial weight of 32 grams and the corrosion rate in specimen B was 0.402641894 mm / year. In specimen C, it experienced a weight reduction of 0.46 grams from the initial weight of 32 grams with a corrosion rate of 0.59746862mm / year. Penelitian ini bertujuan untuk melihat pengaruh perubahan temperatur terhadap laju korosi pada knalpot sepda motor. Pada penelitian eksperimen ini spesimen uji diberi perlakuan panas dengan dibakar langsung menggunakan solder gas, kemudian dicelupkan langsung kedalam wadah yang berisi air biasa dan air garam. Setelah diberi perlakuan (treatment), diadakan evaluasi untuk melihat seberapa besar pengaruhnya. Pada hari ke 12 pengujian seluruh spesimen mengalami penurunan berat, dengan rincian pada specimen A mengalami penurunan berat sebesar 0,5gram dari berat awal 32gram, dengan laju korosi 0,064942241mm/tahun. Spesimen B mengalami penurunan berat sebesar 0,31gram dari berat awal 32 gram dan laju korosi pada spesimen B 0,402641894 mm/tahun. Pada sepesimen C mengalami pengurangan berat sebesar 0,46 gram dari berat awal 32 gram dengan laju korosi 0,59746862mm/tahun.